Bis(ethylenedithio)tetrathiafulvalenium–tetrachloridocobaltate(II) (3/2) - Zhao, Fuqi (International Union of Crystallography, 2008)
The structure of the electrochemically crystallized title compound, (C(10)H(8)S(8))(3)[CoCl(4)](2), consists of two types of bis(ethylenedithio)tetrathiafulvalene (BEDT-TTF) radical cation stacks separated by sheets of tetrahedral [CoCl(4)](2−) anions. One of the BEDT-TTF molecules is generated by inversion. There are short S⋯S contacts between the stacks in the a direction and short C—H⋯Cl contacts between the radical cations and the anions.